2015
DOI: 10.5194/bgd-12-9443-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technical Note: Towards resolving in situ, centimeter-scale location and timing of biomineralization in calcareous meiobenthos – the Calcein-Osmotic pump method

Abstract: Abstract. Insights into oceanographic environmental conditions such as paleoproductivity, sea-surface temperatures, deep-water temperatures, salinity, ice volumes, circulation patterns, and nutrient cycling have all been obtained from geochemical analyses of biomineralized carbonate of marine organisms. However, we cannot fully understand geochemical proxy incorporation and the fidelity of such in species until we better understand fundamental aspects of their ecology such as where and when these (micro)organi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Calcein ( Bis(N , N‐bis (carboxymethyl)aminomethyl)‐fluorescein ) is used to label and distinguish newly grown chambers (Bernhard et al, ), allowing the determination of growth and reproduction under controlled laboratory conditions (e.g., Diz et al, ; Hintz et al, ). Calcein was also used to check the incorporation of trace elements to the new chambers (e.g., de Nooijer et al, ; Evans et al, ; Kramar et al, ; Munsel et al, ; Nardelli et al, ; Van Dijk, de Nooijer, Wolthers, et al, ; van Dijk, de Nooijer, & Reichart, ), to assess the role of fluid‐phase endocytosis in calcification (Bentov et al, ) and in sediment samples to develop a method that can identify the location and timing of calcification (Bernhard et al, ). Possible impacts of calcein were evaluated by Bernhard et al (), Dissard et al (), and Kurtarkar et al (), who found that the marker does not affect the survival rate of individuals, incorporation of elements, nor their growth rates.…”
Section: State‐of‐the‐art On Fluorescent and Fluorogenic Probe Use Inmentioning
confidence: 99%
“…Calcein ( Bis(N , N‐bis (carboxymethyl)aminomethyl)‐fluorescein ) is used to label and distinguish newly grown chambers (Bernhard et al, ), allowing the determination of growth and reproduction under controlled laboratory conditions (e.g., Diz et al, ; Hintz et al, ). Calcein was also used to check the incorporation of trace elements to the new chambers (e.g., de Nooijer et al, ; Evans et al, ; Kramar et al, ; Munsel et al, ; Nardelli et al, ; Van Dijk, de Nooijer, Wolthers, et al, ; van Dijk, de Nooijer, & Reichart, ), to assess the role of fluid‐phase endocytosis in calcification (Bentov et al, ) and in sediment samples to develop a method that can identify the location and timing of calcification (Bernhard et al, ). Possible impacts of calcein were evaluated by Bernhard et al (), Dissard et al (), and Kurtarkar et al (), who found that the marker does not affect the survival rate of individuals, incorporation of elements, nor their growth rates.…”
Section: State‐of‐the‐art On Fluorescent and Fluorogenic Probe Use Inmentioning
confidence: 99%